Rancang Bangun Data Logger Suhu dan Kecepatan Arus Laut Untuk Praktikum Oseanografi - S Suwardi; Liza Lidiawati; Erik Ayatullah (UPT Laboratorium Terpadu, Universitas Diponegoro, 2022)
The equipment of experiment and research of oceanography at the Physics Laboratory of the Faculty of Mathematics and Natural Sciences, Bengkulu University are still very limited of type. One of the oceanography equipment is a current meter to measure the temperature and speed of ocean currents. This equipment has limited data recording which is still manual so that it is prone to human error in its measurement. In an effort to overcome the limitations of the current meter above, in this study a temperature and ocean current velocity data logger was developed. This study aims to develop a data logger and test its effectiveness which was carried out in July – November 2021 with four stages. The first stage is design, including hardware design and software design. The second stage is the manufacturing stage, namely the manufacture of data logger hardware following the system block diagram and software development using Arduino software following the system flow diagram. The third stage is the testing stage, which includes the process of testing system performance, calibration and field testing. The fourth stage is evaluation, namely evaluation of system performance, accuracy of measurement results, and refinement of data loggers. Comparative test of the results of temperature measurements using a data logger and current meter experienced a difference between 0.1 - 0.8 oC. While the current velocity measurement using a data logger and current meter shows a difference between 0.3 – 1 m/s. The data logger has been successfully developed and works well, but its accuracy still needs to be improved by replacing the water velocity sensor with a higher sensitivity.